Factors Influencing Behavioral Intention to Shop Online at Tiktok Shop: A Case Study of Postgraduate Students in Islamic Economics, State Islamic University Sjech M. Djamil Djambek Bukittinggi - Febrina Adita Putri; Rahma Elsa Fitriani; Mardhiyya Azhari; Eka Novia Herdiamy; Al - Amin (Journal on Education, 2023)
Behavioral intentionhas many benefits for companies, one of which is that consumers become loyal online shopping for the products or services they use. The aim of this study was to determine the factors that influence behavioral intentionto shop online at the Tiktok shop. The method in this research is quantitative. Data processing and hypothesis testing used SPSS version 18. This research was conducted on Islamic Economics Postgraduate Students in 2022. Simple Random Sampling was used for sampling. The total population of Postgraduate Islamic Economics students in 2022 is 35 people. The results of this study are that e-service quality has a significant effect on customer satisfaction. It is proven that e-service quality has a significant effect on attitude towards the website. Customer satisfaction has a significant effect on attitude towards the website. Customer satisfaction has a significant effect on behavioral intention. significant to behavioral intention.